Odpowiedź:
Szczegółowe wyjaśnienie:
[tex]a)\\(2x-3)(2x+3)=(x+5)^2-9\\4x^2-9=x^2+10x+25-9\\3x^2-10x-25=0\\\Delta=100+300=400\\\sqrt{\Delta}=20\\x_1=\frac{10+20}{6}=5\\x_2=\frac{10-20}{6}=-1\frac{2}{3}\\\\b)\\2x(x-3)-(x+1)(x+2)=(2x-3)^2\\2x^2-6x-x^2-2x-x-2=4x^2+9-12x\\-3x^2+3x-11=0\\\Delta=9-132<0\\brak\ rozw.\\\\[/tex]
[tex]c)\\(2x-1)^2-(4x+1)(4x-1)=4x(1-2x)\\4x^2-4x+1-16x^2+1=4x-8x^2\\-4x^2-8x+2=0\\\Delta=64+32=96\\\sqrt{\Delta}=\sqrt{96}=4\sqrt6\\x_1=\frac{8+4\sqrt6}{-8}=-1-\frac{1}{2}\sqrt{6}\\x_2=\frac{8-4\sqrt6}{-8}=-1+\frac{1}{2}\sqrt{6}[/tex]